Analisis Penerapan Media Pembelajaran Daring di Sekolah Dasar di Masa Pandemi Covid-19 - Iqnatia Alfiansyah (Universitas PGRI Adi Buana Surabaya, 2021)
The purpose of this study was to analyze the application of online learning media in elementary schools during the Covin-19 pandemic. This research uses a qualitative approach with descriptive research type. This study had as many as 20 educators who were scattered in various areas of the Gresik district who were chosen by the researcher according to the research needs. The learning that is carried out is online learning using gadgets. Problem analysis in this study was obtained using a questionnaire filling instrument via Google Forms and also interviews via the Whatsapp application. The results of this study were that there were several obstacles that occurred related to the implementation of online learning in elementary schools. These problems are in the form of obstacles related to the internet network of educators and students, limited internet quota, and changing learning times.